Knowledge and the Wealth of Nations : A Story of Economic Discovery - Warsh, David (New York W.W. Norton & Company, 2006)
Looks at Paul Romer's 1980s solution of Adam Smith's new growth theory, tracing how the centuries-old puzzle was addressed throughout history and how it has helped leading corporations to address economic expansion and the value of intellectual property.
Include Index.
Keywords: Economics--Research -- Economics -- Research -- United States